Squamous Cell Carcinoma and Merkel Cell Carcinoma: Diagnostic and Therapeutic Management – Expert Opinion of the Polish Dermatological Society - Lesiak, Aleksandra; Szepietowski, Jacek; Czuwara, Joanna; Kamińska-Winciorek, Grażyna; Narbutt, Joanna; Reich, Adam; Kiprian, Dorota; Maj, Joanna; Owczarek, Witold; Owczarczyk-Saczonek, Agnieszka; Rudnicka, Lidia; Walecka, Irena; et al. (Dermatology Review/Przegląd Dermatologiczny, 2024)
The guidelines outline the clinical, pathological, and dermoscopic features of cutaneous squamous cell carcinoma and Merkel cell carcinoma, along with the recommended diagnostic and therapeutic procedures. Surgery remains the primary standard treatment for both cancer types. However, in the case of squamous cell carcinoma, Mohs microsurgery can be additionally used for intraoperative assessment of the radicality of excision. The guidelines also address non-surgical treatment options, including systemic therapies for advanced stages of the disease. The aim of these recommendations is to guide the selection of the most appropriate diagnostic and therapeutic options for individual squamous cell carcinoma and Merkel cell carcinoma patients, based on similar publications from other scientific organizations and the expert opinions of the authors.